Teori Pemerolehan Bahasa dan Implikasinya dalam Pembelajaran - Shafa, Shafa (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2012)
There are two types of language acquisition, Natural and formal. In natural type children usually got their second language through their interaction with their friends when they are playing. For adults, they got their second language through their interaction with their community. The community “force” them to learn or understand the laguage used by the most speaker at the place. So, the person can speak the language without learning from formal school. Indonesia formal type, a learner has to follow the lesson inside of classroom under guidance of teacher. It is not true the statemant said that formal type will have a better result Indonesia language learning. Behavioritic theory told us that language or second language can reach through practicing the language Indonesia speaking. Because of that, someone who wants to master a language has to receive stimulus and answer the stimulus given. But mentalistic theory told us that language is innate owned by human being as a gift inside of their mind. The theory tols us that language is not a habit. Because of that human doesn’t need learn their language. They will master language or second language through interacting with other people. There are 4 factors that influence the language acquisition. First is motivation from inside of the learner. Second is age of the learner. Third is taching and learning process and the last is first language which was masterd by the learner.